How to be happy simple ways to build your confidence and resilience to become a happier, healthier you - Webb, Liggy (Tantor Media, 2020)
How important is it that youre happy' We cant be happy all the time, but happy people get sick less often, have more energy, are better motivated and more creative. Theyre more fun to be around too. So why would you not want to let a little more happiness into your life' Liggy Webb is an expert when it comes to understanding what makes people tick; shes worked with huge companies, national bodies and the United Nations, helping people to develop their confidence, appreciation, resilience and communication so that theyre happier, healthier and more effective. Shes helped people be happier at work and at home, to be more supportive to others and to get where they want to be by changing the way they think. She cant deliver everlasting happiness (not in 250 pages, anyway), but she can distil her amazing approach to developing a better, happier life into practical, encouraging steps which you can apply to your life. So thats what shes done. Learn how to be happy, effective and energetic - and watch how it inspires those around you.
Downloadable audio file
Keywords: Happiness; Self-actualization (Psychology); Business; Affaires; Bonheur; BUSINESS & ECONOMICS / Small Business; Downloadable audio books; Audiobooks; Livres audio